2012
DOI: 10.1155/2012/962183
|View full text |Cite
|
Sign up to set email alerts
|

Betaine Treatment Attenuates Chronic Ethanol-Induced Hepatic Steatosis and Alterations to the Mitochondrial Respiratory Chain Proteome

Abstract: Introduction. Mitochondrial damage and disruption in oxidative phosphorylation contributes to the pathogenesis of alcoholic liver injury. Herein, we tested the hypothesis that the hepatoprotective actions of betaine against alcoholic liver injury occur at the level of the mitochondrial proteome. Methods. Male Wister rats were pair-fed control or ethanol-containing liquid diets supplemented with or without betaine (10 mg/mL) for 4-5 wks. Liver was examined for triglyceride accumulation, levels of methionine cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 41 publications
(68 reference statements)
8
76
1
Order By: Relevance
“…Our laboratory has made seminal contribution in demonstrating that ethanol-induced defects in hepatic transmethylation reactions play a causal role in the pathogenesis of ALD [17][18][19][21][22][23]34]. We have further shown that dietary betaine supplementation, which normalize methylation reactions, protects the liver from many of the ethanol-induced anomalies [17][18][19][20][21][22][35][36][37]. Here, we present novel findings that the alcohol-induced decrease in essential methylation reaction(s) may be a causal factor in disrupting TJ integrity and in promoting intestinal permeability.…”
Section: Discussionmentioning
confidence: 75%
“…Our laboratory has made seminal contribution in demonstrating that ethanol-induced defects in hepatic transmethylation reactions play a causal role in the pathogenesis of ALD [17][18][19][21][22][23]34]. We have further shown that dietary betaine supplementation, which normalize methylation reactions, protects the liver from many of the ethanol-induced anomalies [17][18][19][20][21][22][35][36][37]. Here, we present novel findings that the alcohol-induced decrease in essential methylation reaction(s) may be a causal factor in disrupting TJ integrity and in promoting intestinal permeability.…”
Section: Discussionmentioning
confidence: 75%
“…A separate proteomic study in livers of alcohol-fed rats detected decreases in several mitochondrial proteins involved in oxidative phosphorylation complexes. These decreases were prevented by co-feeding betaine with the ethanol, suggesting that preservation of mitochondrial function may be an additional mechanism by which betaine protects the liver from alcoholic injury [87].…”
Section: Use Of Betaine In Liver Injury Due To Nafld and Aldmentioning
confidence: 98%
“…When MS expression and activity are inhibited by alcohol exposure, betaine becomes an alternate substrate for betaine homocysteine methyltransferase (BHMT) that converts homocysteine to methionine and produces dimethylglycine (DMG) [9] . Recent work in ethanol-fed rats showed that the co-administration of betaine specifically prevented the development of oxidative injury processes through reduction in homocysteine and preservation of normal SAM levels [10] . Methionine, the product of either MS or BHMT, is the substrate for hepatic methionine adenosyl transferase (MAT) which exists in gene form predominantly as MAT1A in progressive alcoholic liver injury and as MAT2A after malignant transformation [8] .…”
Section: Methionine Cycle and Effects Of Ethanolmentioning
confidence: 99%